Menstrual Cycle-Associated Changes in Micronutrient Biomarkers Concentration: A Prospective Cohort Study. Issue 4 (19th May 2023) - Aguree, Sixtus; Murray-Kolb, Laura E.; Diaz, Francisco; Gernand, Alison D.
Abstract: Objective: : To evaluate variations in micronutrient biomarker concentrations and deficiencies across the menstrual cycle in a cohort of healthy women. Methods: : This prospective cohort study was conducted among healthy women of reproductive age living in the State College area, Pennsylvania, ( n  = 45). Data collection occurred at the early follicular phase, the late follicular phase, and the midluteal phase. Fasting blood samples were collected to measure micronutrient biomarkers. Results: : At the early follicular phase, the mean ± SD concentrations for zinc, copper, magnesium, and retinol were 81.8 ± 16.2 µg/dL, 80.1 ± 12.8 µg/dL, 17.9 ± 1.4 mg/L, and 39.4 ± 9.3 µg/dL, respectively. The geometric mean (95% CI) for manganese, iron and ferritin concentrations were 1.51 [1.21, 1.87] µg/L, 106.7 [90.8, 125.4] µg/dL, and 26.4 [20.5, 34.0] µg/L, respectively. Mean concentrations of zinc and magnesium declined by 6.6% ( p  = 0.009) and 4.6% ( p  < 0.001) from the early follicular phase to the midluteal phase, respectively. Other biomarkers remained relatively constant across the cycle. At the early follicular phase, the prevalence of low serum concentrations for zinc, copper, magnesium, manganese, iron, and ferritin was 22%, 7%, 29%, 13%, 14%, and 28%, respectively. Also, in early follicular phase, 36% had anemia, and 13% specifically had iron deficiency anemia. The prevalence of magnesium deficiency was significantly higher at the midluteal phase vs. the early follicular phase ( p  = 0.025). Conclusions: : Our study suggests that while many micronutrient concentrations are relatively constant across the menstrual cycle in healthy women, zinc and magnesium decline, and the prevalence of magnesium deficiency increases. Supplemental data for this article is available online at